STUDENTS’ MOTIVATION TO ATTEND PHYSICAL EDUCATION CLASSES IN UNIVERSITIES OF UKRAINE - Kukhar, Mariana; Sorokolit, Nataliya; Yavorskyy, Andriy; Rymar, Olga; Khanikiants, Olena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article is dedicated to the research of priority motives according to attending “Physical education” classes by I and II year students from universities of Ukraine. The goal of the research is to determine the ratings of students’ motivation towards attending physical education classes in the universities in Ukraine. The methods of research are analysis and generalization of scientific methodologic literature data, sociologic methods (questionnaire) and mathematical statistics methods. The questionnaire was answered by 363 students from 4 Ukrainian universities. Among them were 170 males and 193 females. The main results of the research are as follows. It was determined the general structure of students’ motivation and value orientation according attending physical education classes by each university particularly. There was performed comparable analysis of significance ranking of the motives to attend physical education classes and also generalized differences between females and males in the choice of motivation priority. It was determined that 57,9% of students that have been taking part in the questionnaire, think that priority motive to attend physical education classes is to get credits from the course, while body strengthening has second priority place (47,9%). As males (46,5%) so females (67,9%) believe the most essential motive is to get credits from the course “Physical education” and body strengthening (males – 38,8%, females – 56,6%). The third place among males got the motive to improve physical efficiency (26,5%), among females – the desire to get fit (35,2%). Conclusions: The results we have got testify the importance to increase motivation level to attend physical education lessons.